Incubator for Joper Day Old Chicks with Cohen-Coon PID Controller - Chaidir, Ali Rizal; Widjonarko; Bukhori Muslim (Jurusan Teknik Elektro Universitas Andalas, 2025)
Joper (Jowo Super) chicken parents are generally unable to incubate eggs or provide adequate care for their offspring, making the use of a specialized incubator essential from the hatching phase to Day-Old Chick (DOC) rearing. One of the primary factors contributing to DOC mortality is improper temperature adjustment in the heating system. To ensure optimal early-age development, Joper DOC requires a stable thermal environment within the range of 32°C to 35°C, depending on the growth stage. This study aims to develop an incubator capable of maintaining a constant temperature of 32 °C using Cohen-Coon PID (C-C PID) control while also regulating humidity levels. The proposed incubator integrates an axial fan and an L298N driver, with the temperature and humidity sensors calibrated prior to use. The calibration results show measurement errors of 0.59% for temperature and 5.02% for humidity, indicating high reliability. The application of C-C PID control demonstrates strong performance, characterized by a short rise time (approximately 225 seconds), an acceptable settling time (around 510 seconds), minimal overshoot (1.56%), and a steady-state error approaching 0%. During a 30-minute evaluation period, the system successfully maintained a stable temperature at the 32 °C set point and controlled humidity at below 50% automatically. Furthermore, the incubator design proved effective in practical use, achieving a 0% mortality rate for Joper DOC.